SMART goals setting and biometric changes in obese adults with multimorbidity: Secondary analysis of a randomized controlled trial - Paul Y Takahashi; Stephanie M Quigg; Ivana T Croghan; Darrell R Schroeder; Jon O Ebbert (SAGE Open Medicine, 2019)
Objectives: Clinicians recommend diet and exercise for overweight/obese patients. We conducted a secondary analysis of a randomized controlled clinical trial evaluating goal setting and pedometer use versus usual care on weight, waist circumference, and blood pressure of patients with multiple chronic conditions. Methods: In this trial, we recruited and randomized patients over 18 years with multiple chronic conditions. There were two groups with an immediate intervention group who received behavioral coaching and a pedometer versus a delayed control who received the intervention after 2 months. We evaluated body weight, waist circumference, and blood pressure as outcomes. We used analysis of covariance to evaluate differences between the intervention and the control groups. Results: Of 130 patients, mean age was 63.4 years (SD, 17.3). At 2 months, intervention participants lost 0.2 kg versus a 0.1-kg gain in the control participants ( P  = .44). The immediate intervention group had significantly smaller waist circumference change at 2-month follow-up compared to control at −1.6 cm (95% confidence interval = −3.1 to −0.1), which was driven by an increase in waist circumference in the delayed control group. No difference in systolic blood pressure was observed. Discussion: We observed no difference in weight or blood pressure between the groups with obesity and multiple chronic conditions.